Pengembangan Kewirausahaan Perempuan melalui Inovasi Ecoprint di Desa Ponowareng - Putra, Hega Bintang Pratama; Rahmaningtyas, Avivah; Anggraini, Oktiva; Saputri, Amelia Ayu; Desfiva , Asdya Linka; Adhipermana, Juan (Jurnal Ilmiah Padma Sri Kreshna, 2025)
This training aims to enhance the creativity, productivity, and economic well-being of rural communities by developing skills in ecoprint making. The activity is designed as an effort to empower the community, especially women, so that they are capable of producing marketable products. The training method combines theoretical material delivery with hands-on practice, allowing participants to both understand the basic concepts of ecoprint and apply them in real life. The primary target of this activity is the women of the PKK (Family Welfare Movement) in Ponowareng Village, who have great potential to become agents of change in developing family-based economic initiatives. The ecoprint training in Ponowareng Village was carried out through stages of planning, preparation of materials and tools, and the selection of a suitable venue. The program targets PKK women as the main participants, with the goal of improving their skills and creativity in producing marketable goods. The training method involves a combination of material presentations and live demonstrations. Participants practiced the ecoprint process from arranging leaves to soaking the fabric in an alum solution. The outcomes of the training are expected to foster entrepreneurial potential and improve community welfare. Keywords: ecoprint; entrepreneurship; creativity